A Review of Research : Exploring Ethnomatematics On Indonesian Traditional Games In Mathematics Learning - Adinda Putri Salsabilah; Aida Ar Rahmah; Ayu Wulandari; Joko Soebagyo (Urogram Studi Pendidikan Matematika, Universitas IVET, 2022)
Ethnomathematics is a mathematical concept that exists in a culture. Using ethnomathematics in learning is one of appropriate method. Through learning mathematics that is associated with culture such as traditional games, it create a comfortable learning atmosphere so that students are interested in learning and mathematics seems easy and fun. The positive thing obtained from the concept of ethnomathematics with traditional games is that students can understand the concept and the transfer of values well. This study aims to determine the development of research on ethnomathematics in traditional games. The articles analyzed amounted to 166 of the 370 articles extracted with PoP (Publish or Perish) from the Google Scholar database over a period of 50 years. This research was conducted using bibliometric analysis method using PoP (Publish or Perish) and VOSviewers applications with the keywords